Climate drives temporal replacement and nested‐resultant richness patterns of Scottish coastal vegetation. Issue 8 (14th October 2015) - Lewis, Rob J.; Marrs, Rob H.; Pakeman, Robin J.; Milligan, Gregg; Lennon, Jack J.
Abstract : Beta diversity quantifies spatial and/or temporal variation in species composition. It is comprised of two distinct components, species replacement and nestedness, which derive from opposing ecological processes. Using Scotland as a case study and a β‐diversity partitioning framework, we investigate temporal replacement and nestedness patterns of coastal grassland species over a 34‐yr time period. We aim to 1) understand the influence of two potentially pivotal processes (climate and land‐use changes) on landscape‐scale (5 × 5 km) temporal replacement and nestedness patterns, and 2) investigate whether patterns from one β‐diversity component can mask observable patterns in the other. We summarised key aspects of climate driven macro‐ecological variation as measures of variance, long‐term trends, between‐year similarity and extremes, for three important climatic predictors (minimum temperature, water‐balance and growing degree‐days). Shifts in landscape‐scale heterogeneity, a proxy of land‐use change, was summarised as a spatial multiple‐site dissimilarity measure. Together, these climatic and spatial predictors were used in a multi‐model inference framework to gauge the relative contribution of each on temporal replacement and nestedness patterns. Temporal β‐diversity patterns were reasonably well explained by climate change but weakly explained by changes in landscape‐scale heterogeneity. Climate was shown to have a greater influence on temporal nestedness than replacement patterns over our study period, linking nestedness patterns, as a result of imbalanced gains and losses, to climatic warming and extremes respectively. Important climatic predictors (i.e. growing degree‐days) of temporal β‐diversity were also identified, and contrasting patterns between the two β‐diversity components revealed. Results suggest climate influences plant species recruitment and establishment processes of Scotland's coastal grasslands, and while species extinctions take time, they are likely to be facilitated by climatic perturbations. Our findings also highlight the importance of distinguishing between different components of β‐diversity, disentangling contrasting patterns than can mask one another.